Ustanowić wartości. Problematyka aksjologiczna w „Głosie Pana" Stanisława Lema - Krupecka, Iwona (Przestrzenie Teorii, 2007)
His Master's Voice's protagonist passes through the levels of the evolution "to values" referring to those described by Nietzsche. The starting point are childish skirmishes with God, consisting in experiments with values established in Western culture. In the same time the character keeps obligatory rules because of Nietzscheanian "must". Another level is positive nihilism in which the protagonist replaces values by statistic concepts. The last, the most important, is the moment of recognition of "cosmic letter"'s senders as representatives of "favoring virtue", and this act expresses Nietzscheanian "want".